Variability of somatic clones induced from tea microsprouts callus tissue (Camellia sinensis (L.) O. Kuntze) in Vitro culture - M. V. Gvasalia (Новые технологии, 2018)
Morphometric parameters of somatic clones induced from the callus culture of of the local tea population microsprouts have been studied. Under conditions of long-term (7 years) cultivation in vitro, with additional mutational load, in the form of exogenous growth regulators and other factors, somaclonal variability increases and almost all the main morphological features of tea microshoots are affected. 15 tea somaclones have been selected, which exceeded the initial control phenotype (local population) by a complex of morphological characters and may be involved in the selection process.